PLAIN LANGUAGE SOLUTIONS TO THE PROBLEMS OF LEGALESE — A CASE STUDY OF WILLS - BOLESZCZUK, Emilia (Comparative Legilinguistics, 2017)
Legal English is well-known for its complexity which makes it incomprehensible for lay readers. The answer to the problem of legalese is the plain English movement, aiming at simplification of the language of documents. Despite the fact that the rules for clearer drafting have been extensively discussed, there are still no uniform standards, which is one of the factors that delay the pace of reform. Some types of documents, e.g. wills, are especially resistant to the reform. The aim of this paper is to present a comparative analysis of legalese and plain English on the example of one type of texts. The material comprises a set of 6 British wills: 3 written in traditional style and3 inplain English. The analysis takes into account both macrostructure and microstructure of wills, including design and layout, grammatical structures and lexicon. The analysis reveals that plain language wills are much more readable than their legalese counterparts, as they use better organization, more accessible grammatical structures, and less ambiguous and less archaic terminology. It is argued that it is worthwhile to work on the enhancement of the existing plain language strategies and solutions, so as to develop and popularize plain legal English.